Trimetallic nanostructures: The case of AgPd-Pt multiply twinned nanoparticles - Khanal, Subarna (2013)
We report the synthesis, structural characterization, and atomistic simulations of AgPd-Pt trimetallic (TM) nanoparticles. Two types of structure were synthesized using a relatively facile chemical method: multiply twinned core-shell, and hollow particles. The nanoparticles were small in size, with an average diameter of 11 nm and a narrow distribution, and their characterization by aberration corrected scanning transmission electron microscopy allowed us to probe the structure of the particles at an atomistic level. In some nanoparticles, the formation of a hollow structure was also observed, that facilitates the alloying of Ag and Pt in the shell region and the segregation of Ag atoms on the surface, affecting the catalytic activity and stability. We also investigated the growth mechanism of the nanoparticles using grand canonical Monte Carlo simulations, and we have found that Pt regions grow at overpotentials on the AgPd nanoalloys, forming 3D islands at the early stages of the deposition process. We found very good agreement between the simulated structures and those observed experimentally. © 2013 The Royal Society of Chemistry.